2018
DOI: 10.11591/ijere.v7i2.12770
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Method Research on Peer Assessment

Abstract: The purpose of this study is to investigate the relationship between peer assessment and instructor assessment and make a comparison with views of preservice teachers. Since qualitative and quantitative methods were used together in the study, it was grounded on the mixed method approach. The quantitative data in this study, in which 27 preservice teachers participated on a voluntary basis, were obtained from scoring rubric whereas qualitative data were obtained from a semi-structured interview form prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In studies conducted with university students (Dundar, 2016;Gurbuzoglu-Yalmanci, 2016;Hasirci, 2018;Izgar & Akturk, 2018;Sarpkaya-Aktas, 2017), it was revealed that students did not trust their peers' evaluation. In the study by Cheng & Warren (2005), it was determined that university students studying in the engineering department did not rely on their own language competences while evaluating their friends during their oral presentations and did not make an objective assessment because they did not have a command of these competences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted with university students (Dundar, 2016;Gurbuzoglu-Yalmanci, 2016;Hasirci, 2018;Izgar & Akturk, 2018;Sarpkaya-Aktas, 2017), it was revealed that students did not trust their peers' evaluation. In the study by Cheng & Warren (2005), it was determined that university students studying in the engineering department did not rely on their own language competences while evaluating their friends during their oral presentations and did not make an objective assessment because they did not have a command of these competences.…”
Section: Discussionmentioning
confidence: 99%
“…Peer evaluation includes tasks that require time for reflection, comparison and communication (Topping, 1998). Studies on the negative aspects of peer evaluation (Cheng and Warren, 2005;Dundar, 2016;Gurbuzoglu-Yalmanci, 2016;Hamzadayi and Dolek, 2017;Hasirci, 2018;Izgar and Akturk, 2018;Ozdemir and Erdem, 2017;Panadero and Brown, 2017;Sarpkaya-Aktas, 2017) indicate that there is a problem of objectivity in peer evaluation. Peer and self-evaluation approaches also play an important role in teacher training programs and can positively affect pre-service teachers' professional lives by improving their academic performance (Roberts, as cited in Aslanoglu, 2017).…”
Section: Peer Evaluationmentioning
confidence: 99%
“…ere are a lot of survey studies revolving around assessments which are about the nature of assessments, including summative assessment and the formative assessment and the impact on students learning performance, motivation, and provide high-quality learning [6,23,24]. It is also seen that there are numerous studies on peer, and self-assessment arrived at the conclusion that peer, and self-assessment promoted student success, their participation in course and skills [25][26][27][28]. However, there is very modest elaboration in how to design assessment practices and make reliable judgments.…”
Section: An Overview On Assessment and Its Typesmentioning
confidence: 99%
“…It will affect the quality of the scores. Furthermore, some results of peer assessment are dubious (Izgar & Akturk, 2018). However, Topping (1998) argued that undergraduate students have mature age and are able to think and to be trusted.…”
Section: Introductionmentioning
confidence: 99%